Development of a Management Plan for the Municipal Ecological Structure - João Corgo (Universidade do Porto, 2021)
In a world increasingly urbanized, management of cities and spatial planning take an important place in political and technical concerns, and it is in this perspective that the Municipal Ecological Structure (MES) arises in Portugal’s urban planning system. However, this instrument still struggles with some delimitation, regulation and management issues, that challenge its implementation. In order to overcome these problems, this article wants to explore the designing hypothesis of a Management Plan for the Municipal Ecological Structure (MPMES). To support the plan, this study explores the role of ecosystem services and their potential to provide a vision of the value of Municipal Ecological Structure to the territories, to the people, and as an impulse for local sustainable economic growth. In order to gather insights on the contribution of the management plan for the Municipal Ecological Structure implementation, an approach was made, based on interviews, confronting visions and discourses, by planning experts’ contrasts with the stakeholders. Therefore, it was possible to identify, characterize and value the functions performed by the Municipal Ecological Structure of Sesimbra. Ultimately, the objectives, contents, development, approval and articulation with other territorial management instruments were identified as requirements for the Management Plan for the Municipal Ecological Structure development.